Jasa (Al-Wakalah) - Muhammad Naufal Sanyoto; Virna Aulia Rahmah; Nadhifah Umar (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2025)
Al-Wakalah is one of the contracts in Islamic jurisprudence that allows the delegation of authority from one party to another to conduct certain activities permitted by Sharia. This contract has developed significantly alongside the increasing demand for modern financial services, particularly in Islamic banking. This paper explores the fundamental concept of al-wakalah, its legal foundations in Islam, the essential elements and conditions of the contract, the various types of wakalah, and its applications in banking practices. The study employs a library research method by examining classical fiqh literature as well as contemporary academic sources. The findings indicate that al-wakalah is not only applied in personal transactions but also plays a strategic role in various banking services such as trade financing, fund transfers, investment management, and Islamic insurance. Therefore, al-wakalah serves as a crucial instrument in strengthening the Islamic financial system by ensuring transparency, security, and compliance with Sharia principles.